Preparation and Characterizations of In0.1SnxZn0.85-2xS Powder Photocatalysts for Hydrogen Production under Visible Light Irradiation - Kimi, Melody; Leny, Yuliati; Mustaffa, Shamsuddin (Trans Tech Publications, 2012)
A series of In0.1SnxZn0.85-2xS solid solutions was synthesized by hydrothermal method and employed as photocatalyst for photocatalytic hydrogen evolution under visible light irradiation. The structures, optical properties and morphologies of the solid solutions were studied by X-ray diffraction, diffuse reflectance UV–visible spectroscopy and field emission scanning electron microscopy. From the characterizations, it was confirmed that In0.1SnxZn0.85-2xS solid solution can be obtained and they have nano-sized particles. The highest photocatalytic activity was observed on In0.1Sn0.03Zn0.79S photocatalyst, with average rate of hydrogen production 3.05 mmol/h, which was 1.2 times higher than the In0.1Zn0.85S photocatalyst.